Gentamicin-loaded exosomes from IMMUNEPOTENT CRP enhance healing of infected diabetic wound in mice - García Coronado, Paola Leonor; Garza Martínez, Brandon Alberto; Moreno Amador, Kenia Arisbe; Reding Hernández, David; Zárate Triviño, Diana G.; Caballero Hernández, Diana Elia; Zapata Benavides, Pablo; Luna Barcenas, Gabriel; Rodríguez‐Padilla, Cristina; Franco Molina, Moisés Armides (Frontiers in Pharmacology, 2025)
IntroductionDiabetic foot infections (DFIs) are a major cause of lower extremity amputations and are associated with substantial morbidity and reduced quality of life. Given the limited efficacy of current treatments and the rise of antimicrobial resistance, there is an urgent need for innovative therapeutic approaches. This study evaluates the use of exosomes derived from a bovine leukocyte spleen extract (IMMUNEPOTENT CRP), loaded with gentamicin, to improve infection control and promote wound healing in a diabetic setting.MethodsThe efficiency of gentamicin encapsulation were evaluated followed by gentamicin release under acidic and alkaline conditions. A wound model was established in streptozotocin (STZ)‐induced diabetic mice, followed by inoculation with Staphylococcus aureus to simulate infected diabetic ulcers. Mice were treated with gentamicin-loaded exosomes (Exo‐Genta), IMMUNEPOTENT CRP‐derived exosomes (ICRP-Exo), or free gentamicin. Wound closure was assessed for 21 days. On days 0, 7, 14, and 21 skin tissue samples were collected from treated mice to evaluate epithelial thickness, area, and cell number calculation by hematoxylin and eosin (H&E); collagen synthesis, and PI3K-AKT pathway activation, beside skin samples, blood samples were collected to quantify pro‐inflammatory cytokine levels.ResultsThe Exo‐Genta and IMMUNEPOTENT CRP significantly enhanced collagen fiber deposition, blood vessel formation, and hair follicle regeneration. At the molecular level, these treatments increased AKT phosphorylation and modulated the inflammatory response, with reduced levels of TNF‐α, IL‐6, and MCP‐1, alongside a significant increase in anti-inflammatory IL‐10.ConclusionsGentamicin‐loaded exosomes derived from IMMUNEPOTENT CRP demonstrated enhanced antimicrobial activity and tissue regeneration in infected diabetic wounds. These findings support their potential as an effective and less invasive therapeutic strategy for diabetic foot ulcers by combining infection control and pro‐regenerative and immunomodulatory effects.